2005
DOI: 10.1021/es050884s
|View full text |Cite
|
Sign up to set email alerts
|

Humic Material Induces Behavioral and Global Transcriptional Responses in the Nematode Caenorhabditis elegans

Abstract: Humic materials are complex organic molecules constituting the most abundant source of natural organic matter (NOM) in freshwater and soil ecosystems. Recent advances have identified that they interfere with biological systems, via the induction of biotransformation enzymes, the inhibition of photosynthetic oxygen release (in freshwater plants), the production of internal oxidative stress, or through the feminization of fish and amphibians. The nematode model organism Caenorhabditis elegans was chosen to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 51 publications
(56 reference statements)
2
44
2
Order By: Relevance
“…Consequently, it is assumed that the SOM itself acted as natural xenobiotics in relation to their interactions with the biota-in analogy to secondary plant compounds (Li et al 2007); yet, in contrast to the latter, HSs are not synthesized to defend against herbivory, but challenge any exposed organism (Timofeyev et al 2004(Timofeyev et al , 2006Menzel et al 2005b;Bedulina et al 2010). Indeed, HSs as the major part of P have a variety of functional groups, which resemble xenobiotic chemicals.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it is assumed that the SOM itself acted as natural xenobiotics in relation to their interactions with the biota-in analogy to secondary plant compounds (Li et al 2007); yet, in contrast to the latter, HSs are not synthesized to defend against herbivory, but challenge any exposed organism (Timofeyev et al 2004(Timofeyev et al , 2006Menzel et al 2005b;Bedulina et al 2010). Indeed, HSs as the major part of P have a variety of functional groups, which resemble xenobiotic chemicals.…”
Section: Resultsmentioning
confidence: 99%
“…Attraction assay NGM agar plates (92 mm) were prepared, in accordance to Menzel et al (2005), with six alternating spots of bacteria, lacking or supplemented with PPs (Q 200 lM, CA 300 lM, RA 200 lM). One L4 juvenile F1 worm was placed on each of the six spots and, following incubation for 72 h at 20°C, the number of F2 offspring on each individual spot determined.…”
Section: Growth Alterationsmentioning
confidence: 99%
“…Such responses have, moreover, been linked to specific genes and pathways. Under field conditions abiotic stress is, however, seldom uni-dimensional, thus the task of defining transcriptional norms and deciphering molecular genetic response pathways is considerably more challenging (Steinberg et al 2008), although not impossible as demonstrated by studies on humic substances (Menzel et al 2005) and river sediment mixture toxicity .…”
Section: Transcriptional Reaction Norms and Abiotic Stress Within A Gmentioning
confidence: 99%